Analysis and simulations of optimal geometry shapes of the 4 and 9 nano hole arrays (NHAs) with surface plasmonics and optical properties of biosensors systems - Ahmed hussein Duhis; Mohanad Aljanabi (Institute of Advanced Engineering and Science, 2020)
The possibility to limit and manipulate photons at nanometer scales attracted a lot of interest for exciting applications from subwavelength in laser, biosensors, biomedical and optoelectronics devices, the sensor optical properties, however; are complex due to two resonances through propagating and localized surface plasmons. The optical properties of surface plasmons (SPs) at the resonant wavelength is depending on the geometrical nanostructure of materials. In this article, we used different geometry of nanoholes array, 4 and 9 nanoholes array in a metallic film gold nanoparticle with different thickness (20,50,100) nm on SiO2 substrate with refractive index 1.46, we designed two different geometries; 4- holes: hole radius r1=200 nm, period p1=600 nm; and 9- holes: r2=100 nm, period p2=300 nm. Transmission and reflection spectrum have been calculated and simulated by FDTD Lumerical program. From results are observed the effect of thickness is interesting, transmission is increased at (t=20nm) for two arrays. Furthermore, the number of hole and its area has an influence on optical transmission and other parameters (E, H, Ref) which are characteristics of design of metallic nanostructure. We can see that there is a peak value of the wavelength at 519 nm approximately to 73% strong light transmission with 4-NHA in the other hand wavelength of 519 nm transmission is 45% with 9-NHA. strong light transmission is hopeful for many applications (biomedical devices, nanoantennas and laser optical fiber).